2022
DOI: 10.3389/fmed.2021.803929
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognostic Value of Tertiary Lymphoid Organs in Membranous Nephropathy: A Retrospective Study

Abstract: BackgroundTertiary lymphoid organs play an essential role in the inflammation of the kidney. The clinical association between TLOs and membranous nephropathy (MN) is not clear yet.MethodsConsecutive patients with the histologically confirmed membranous nephropathy in Tongji Hospital from July 19, 2012, to September 26, 2019, were included in this study. TLOs in renal biopsy tissues were detected by periodic acid–Schiff-stained and immunohistochemistry. Logistic regression was performed to evaluate the correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition, T cells and macrophages are the main infiltrating cells in PMN [ 52 , 53 ]. For example, in some patients, even tertiary lymphoid structure could be observed which were associated with the severity of clinical features [ 54 ]. T cells and myeloid cells were the dominant immune cells, which was also found in the report of Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, T cells and macrophages are the main infiltrating cells in PMN [ 52 , 53 ]. For example, in some patients, even tertiary lymphoid structure could be observed which were associated with the severity of clinical features [ 54 ]. T cells and myeloid cells were the dominant immune cells, which was also found in the report of Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney. TLSs can be induced in CKDs, including IgA nephropathy [158][159][160] , lupus nephritis 65 , IgG4-related kidney diseases 161 , interstitial nephritis 162,163 , membranous nephropathy 164 and antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis 165,166 as well as in kidney allografts 37,39,44,[167][168][169][170] . Clinical studies have demonstrated that TLS formation is associated with poor kidney outcomes in these diseases (Supplementary Table 2).…”
Section: Chronic Inflammatory Diseases and Ageingmentioning
confidence: 99%
“…Studies in patients with IgA nephropathy have reported that TLSs were detected in 30-40% of participants and were associated with higher levels of serum creatinine, proteinuria and blood pressure, greater severity of glomerulonephritis and future disease progression [158][159][160] . A study in patients with membranous nephropathy reported that TLSs were detected in 34.2% of participants and were associated with higher levels of serum creatinine, proteinuria and blood pressure, lower serum albumin concentrations and lower remission rates 164 . Notably, a higher proportion of patients with membranous nephropathy who had renal TLSs had anti-PLA2R autoantibodies than those without TLSs (72.5% versus 47.4%) 164 .…”
Section: Chronic Inflammatory Diseases and Ageingmentioning
confidence: 99%
See 1 more Smart Citation